Ekspresi EBNA-1 pada diffuse large B cell lymphoma serta Small lymphocytic lymphoma tipe nodal dan ekstranodal - . Indrawati; . Irianiwati; . Harijadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2006)
EBNA-1 expression in nodal and extranodal type of diffuse large B cell lymphoma and small lymphocytic lymphoma Background : Diffuse large B cell lymphoma is the most common type of non-Hodgkin lymphoma. Epstein-Barr Virus infection has been suggested to be involved in the pathogenesis of non-Hodgkin lymphoma. Objective : To know the expression of EBNA-1 in diffuse large B cell lymphoma and small lymphocytic lymphoma and its association with nodal and extranodal location of B cell non-Hodgkin lymphoma Methods : Thirty five cases of B cell non-Hodgkin lymphoma from embedding parafin tissue were constituted the basis of the study. Immunohistochemical examination using CD20 and EBNA-1 monoclonal antibody was done. The difference of EBNA-1 expression between diffuse large B cell lymphoma and small lymphocytic lymphoma and the difference of EBNA-1 expression between nodal and extranodal locations of B cell non-Hodgkin lymphoma were analized by chi square test Result and Conclusion : Sixteen cases of B cell non-Hodgkin lymphoma showed positivity of EBNA-1 expression. There was significant difference between the number of cases with positivity of EBNA-1 expression in nodal and extranodal location of B cell non-Hodgkin lymphoma. There was not significant difference between the number of cases with positivity of EBNA-1 expression in diffuse large B cell lymphoma and small lymphocytic lymphoma. The result supported that latency EBV related lymphoma frequently occurs in extranodal location Key words : EBNA-1, diffuse large B cell lymphoma, small lymphocytic lymphoma, nodal, extranodal